Pengaruh Pengukusan dan Perendaman dengan NaOH terhadap Pelengkungan Kayu Rasamala (Altingia excelsa Noronha), Asam Jawa (Tamarindus indica L.) dan Marasi (Hymeneae courbaril L.) The Influence of Steaming and Soaking in NaOH to Bending of Rasamala (Altingia excelsa Noronha), Java Tamarind (Tamarindus indica L.) and Marasi (Hymeneae courbaril L.)Wood - Jamaludin Malik; K. Yuniart; Jasni Jasni; O. Rachman (Masyarakat Peneliti Kayu Indonesia, 2006)
Wood bent has been observed on three wood species from forest people plantation, i.e. Rasamala (Altingia excelsa Noronha), Java Tamarind (Tamarindus indica L.) and Marasi (Hymenaea courbaril L.), through steaming and soaking in 3% NaOH pre-treatment.The results showed that pre-treatment by soaking in 3% NaOH for 7 days continued by steaming for 30 minutes at temperature of 105 + 3ºC, could increase bent ability of each wood as follows: Rasamala 124%, Marasi 41% and Java Tamarind wood 13%, compared to bent ability of these woods with steaming treatment only. The Rasamala wood has bigger bent-radius or more difficult to be bent than the two others. Bending radius and increasing of wood bending of wood with high specific gravity is lower than wood with low the specific gravity